A new attribution to the Pietro di Giovanni Lianori’s catalog - Paolo Cova (Intrecci d'arte, 2013)
The article concerns a new attribution to the Pietro di Giovanni Lianori's catalog: an interesting mural painting with the bust of St. Thomas d'Aquino. The fragment of fresco was ignored by the critics. The St. Thomas has been moved to different parts of San Domenico in Bologna, maybe for devotional motives and today it is wall up in convent. The artistic and historical analysis would like to correctly enter the work in Lianori's catalog. Article would also like to reconnect the fresco with another Lianori's testimony painting: a Madonna with saint preserved in the little museum of San Domenico. Finally, the aim is also reflecting about some stylistic aspects of Lianori's artistic production, while particularly important in Bologna is the influence of Late Gothic painting of Giovanni da Modena.